Sosialisasi Penataan Rumah yang Rapi Menggunakan Fischer di Kecamatan Sematang Borang - Mahmud Basuki; Selvia Aprilyanti; Winny Andalia; Hermanto MZ; Azhari (Universitas Lancang Kuning, 2021)
Implementation of community service (PKM) carried out in Sukamulya Village, Sematang Borang Subdistrict, Palembang City was motivated by a lack of knowledge and understanding of the community regarding physical aids in residential structuring. Fischer or viser is a tool for connecting screws made by plastic material that is commonly used for household installation purposes such as installing shelves, curtains, TV briquettes and so forth. The PKM method is carried out through socialization, the practice of installing a physical exam and a survey of material understanding using a questionnaire. The results of the socialization showed 75% more understanding and knowledge of the people of Sukamulya Village on the installation of fischer in the arrangement of the house to make it more presentable.